Baccaurea angulata fruit juice ameliorates altered hematological and biochemical biomarkers in diet-induced hypercholesterolemic rabbits - Ahmed, Idris Adewale; Abimbola Mikail, Maryam; Ibrahim, Muhammad (Elsevier Inc., 2017)
Hypercholesterolemia is an important risk factor linked to the alteration of blood hematology and clinical chemistry associated with the development and progression of atherosclerosis. Previous studies have demonstrated the safety and potential health benefits of Baccaurea angulata (BA) fruit. We hypothesized that the oral administration of BA fruit juice could ameliorate the alteration in the hematological and biochemical biomarkers of diet-induced hypercholesterolemic rabbits. The aim of this study was to investigate the effects of different doses of BA juice on the hematological and biochemical biomarkers in normo- and hypercholesterolemic rabbits. Thirty-five healthy adult New Zealand White rabbits were assigned to seven different groups for 90 days of diet intervention. Four atherogenic groups were fed a 1% cholesterol diet and 0, 0.5, 1.0, and 1.5 mL of BA juice per kg of rabbit daily. The other three normal groups were fed a commercial rabbit pellet diet and 0, 0.5, and 1.0 mLof BA juice per kg of rabbit daily. Baseline and final blood samples after 90 days of repeated administration BA juice were analyzed for hematological parameters while serum, aortic and hepatic lysates were analyzed for lipid profiles and other biochemical biomarkers. The alteration of the hemopoietic system, physiological changes in serumand tissues lipid profiles and other biochemicals resulting from the consumption of a high-cholesterol diet were significantly (P < .05) ameliorated by the administration of BA juice. Improvements of the biomarkers in rabbits were dose-dependent, markedly enhanced at the highest dose of juice (1.5 mL/kg/day). The results suggest potential health benefits of the antioxidant-rich BA fruit juice against hypercholesterolemia-associated hematological and biochemical alterations in the rabbit.